Durvalumab-induced diabetic ketoacidosis followed by hypothyroidism. (12th December 2019) - Patel, Shivani; Chin, Venessa; Greenfield, Jerry R
Abstract : Summary: Durvalumab is a programmed cell death ligand 1 inhibitor, which is now approved in Australia for use in non-small-cell lung and urothelial cancers. Autoimmune diabetes is a rare immune-related adverse effect associated with the use of immune checkpoint inhibitor therapy. It is now being increasingly described reflecting the wider use of immune checkpoint inhibitor therapy. We report the case of a 49-year-old female who presented with polyuria, polydipsia and weight loss, 3 months following the commencement of durvalumab. On admission, she was in severe diabetic ketoacidosis with venous glucose: 20.1 mmol/L, pH: 7.14, bicarbonate 11.2 mmol/L and serum beta hydroxybutyrate: >8.0 mmol/L. She had no personal or family history of diabetes or autoimmune disease. Her HbA1c was 7.8% and her glutamic acid decarboxylase (GAD) antibodies were mildly elevated at 2.2 mU/L (reference range: <2 mU/L) with negative zinc transporter 8 (ZnT8) and islet cell (ICA) antibodies. Her fasting C-peptide was low at 86 pmol/L (reference range: 200–1200) with a corresponding serum glucose of 21.9 mmol/L. She was promptly stabilised with an insulin infusion in intensive care and discharged on basal bolus insulin. Durvalumab was recommenced once her glycaemic control had stabilised. Thyroid function tests at the time of admission were within normal limits with negative thyroid autoantibodies. Four weeks post discharge, repeat thyroid function tests revealed hypothyroidism, with an elevated thyroid-stimulating hormone (TSH) at 6.39 mIU/L (reference range: 0.40–4.80) and low free T4: 5.9 pmol/L (reference range: 8.0–16.0). These findings persisted with repeat testing despite an absence of clinical symptoms. Treatment with levothyroxine was commenced after excluding adrenal insufficiency (early morning cortisol: 339 nmol/L) and hypophysitis (normal pituitary on MRI). Learning points: Durvalumab use is rarely associated with fulminant autoimmune diabetes, presenting with severe DKA. Multiple endocrinopathies can co-exist with the use of a single immune checkpoint inhibitors; thus, patients should be regularly monitored. Regular blood glucose levels should be performed on routine pathology on all patients on immune checkpoint inhibitor. Clinician awareness of immunotherapy-related diabetes needs to increase in an attempt to detect hyperglycaemia early and prevent DKA.